Waste Reduction in Fertilizer Manufacturing Through Lean Six Sigma and 5S Implementation - Meisufi, Ruro Wiranti; Rochmoeljati, Rr. (Newinera Publisher, 2025)
This study aims to analyze the waste that occurs in the fertilizer production process at PT XYZ and provide suggestions for improvement with the Lean Six Sigma approach and the 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). Data was collected through observation, interviews, and questionnaires, then analyzed using the DMAIC stages and tools such as Value Stream Mapping, RCA, and VALSAT. The results showed the three highest wastes were defects, motion, and transportation, with an average DPMO value of 32,706.67 and a sigma level of 3.43. The proposed improvements focused on implementing 5S to increase work efficiency and reduce non-value-added activities. After the improvement, the process efficiency value increased by 6.86%, indicating the effectiveness of the applied method.